O backstage em cena: uma análise do presenteísmo no ensino virtual síncrono durante a pandemia da Covid-19 - Vieira, Nelinho de Jesus (2023)
The Covid-19 pandemic interfered in the context of education. The necessity of social isolation was reflected in the teaching and learning process, allowing methodologies mediated by information technologies with remote and synchronous classes to become the main means to continue the process. This new reality imposed on institutions was quickly reflected in the adaptation of all those involved in the educational context in the virtual environment. Thus, with this study, we aimed to understand how presenteeism manifested itself in the behavior of academics in accounting courses during the period of remote and synchronous classes in the conjuncture of the Covid-19 pandemic, from the perspective of role playing. We adopted a qualitative approach and used Discourse Analysis, considering the Goffmanian perspective. In this work, we consider the years 2020 and 2021, having as research subjects students and professors of accounting courses at Brazilian public and private higher education institutions. In the analyses, we contemplated five dimensions of Goffman's dramaturgy (2014) that were explored from the perspective of the research subjects, of which, three were used to analyze the discourse of teachers and students, namely: (i) Stage: space of representation; (ii) Representation: costumes and script; (iii) Audience: audience watching the show. The dimension (iv) Backstage: what was not accessible to the public was considered for the teachers and the dimension (v) Space of the performance: virtualization and inaccessibility, was considered for the students. The results showed that the implementation of classes through technologies enabled the virtualization of the learning process, which caused the student to move away to other spaces of representation at the same time that remote classes were taking place. To stay away from the space intended for learning, students developed innovative facades that were sustained through representation mechanisms. In this new reality, the phenomenon of virtualism manifests itself, which we describe as the behavior in which the academic remains connected to the virtual class platform, but does not fully concentrate on the class being taught in the digital environment. Virtualist behavior contributed to the expansion of different stages of representation in the educational virtual environment, that is, virtualism allowed students the freedom to interact in other interactional spaces, simultaneously with the remote class. Based on these results, this study theoretically contributes to the development of future research, as we reach a theoretical depth on the phenomenon of virtualism in the educational process. We use a not much explored theory in accounting studies and present explanations about the interactional process in remote and synchronous classes. In this sense, it can help in analyzes of other areas of knowledge. This research also presents practical contributions, for the reason that we develop a form of analysis through a logical sequence, from the perspective dramaturgy, which can be useful in carrying out future investigations. Still, it can help in the development of new methodologies aimed at improving the teaching and learning process.